OPTIMIZATION AND ROUTING OF PEDIATRIC PATIENTS WITH SUSPECTED CNS TUMORS - Polatova Djamila Shagayratovna; Xojayev Shoxrux Qaxorbek ugli; Saloxiddinov Habibullo Adhamjon ugli (European Science Publishing, 2025)
Optimization and Routing of Pediatric Patients with Suspected CNS Tumors